Dielectric relaxation and electrical conduction in (BixNa1−x)0.94Ba0.06TiO3 ceramics. Issue 2 (13th October 2017) - Li, Xiaojuan; Jing, Qi; Xi, Zengzhe; Liu, Peng; Long, Wei; Fang, Pinyang
Abstract: The dielectric relaxation and electrical conduction were investigated in (Bi x Na1− x )0.94 Ba0.06 TiO3 (Abb. x BNBT6, x = 0.5, 0.495, 0.485, and 0.475) ceramics prepared by solid state reaction. With a decrease in x, the dielectric properties of the ceramics decreased, whereas the electrical conduction increased, resulting in a transition from insulator to oxide‐ions conductor. When x = 0.475, the ceramics exhibited large conductivity ( 10 −3 S cm −1 at 575°C) and low activation energy ( 0.45 eV), indicating their potential application in solid oxide fuel cells. A mixed conduction mechanism with oxide‐ions, electrons, and holes was proposed. With a decrease in x from 0.495 to 0.475, it was found that the p ‐type conduction was switched to n ‐type conduction. The dielectric relaxation of the x = 0.495 sample was associated with short‐range hopping of oxygen vacancies. However, the dielectric properties of the x = 0.485 and 0.475 samples can be explained by Maxwell‐Wagner interface relaxation.